Levels of insecticide resistance and resistance mechanisms in Aedes aegypti from some Latin American countries - Rodríguez, María M; Bisset, Juan A; Fernández, Ditter (Journal of the American Mosquito Control Association, 2007)
Eight Latin American strains of Aedes aegypti were evaluated for resistance to 6 organophosphates (temephos, malathion, fenthion, pirimiphos-methyl, fenitrothion, and chlorpirifos) and 4 pyrethroids (deltamethrin, lambdacyhalothrin, betacypermethrin, and cyfluthrin) under laboratory conditions. In larval bioassays, temephos resistance was high (resistance ratio [RR50], > or =10X) in the majority of the strains, except for the Nicaragua and Venezuela strains, which showed moderate resistance (RR50, between 5 and 10X). The majority of the strains were susceptible to malathion, fenthion, and fenitrothion. However, resistance to pirimiphos-methyl ranged from moderate to high in most of the strains. Larvae from Havana City were resistant to 3 of the pyrethroids tested and moderately resistant to cyfluthrin. The Santiago de Cuba strain showed high resistance to deltamethrin and moderate resistance to the other pyrethroids (lambdacyhalothrin, betacypermethrin, and cyfluthrin). The rest of the strains were susceptible to pyrethroids, except for the Jamaica and Costa Rica strains, which showed moderate resistance to cyfluthrin, and Peru and Venezuela, which showed resistance to deltamethrin. Adult bioassays showed that all the strains were resistant to dichlorodiphenyl-trichloroethane and to the majority of pyrethroids evaluated. The use of the synergists S,S,S,-tributyl phosphorotrithioate and piperonil butoxide showed that esterase and monooxygenases played an important role in the temephos, pirimiphos-methyl, and chlorpirifos resistance in some strains. Biochemical tests showed high frequencies of esterase and glutathione-S-transferase activity; however, the frequency of altered acetylcholinesterase mechanism was low. The polyacrylamide electrophoresis gel detected the presence of a strong band called Est-A4. Insecticide resistance in Ae. aegypti is a serious problem facing control operations, and integrated control strategies are recommended to help prevent or delay the temephos resistance in larvae and pyrethroids resistance in adults.